(untitled) (Turkish Journal of Computer and Mathematics Education (TURCOMAT), 2021)
Organizing library materials cannot be separated from the application of the classification system which is used as a class-based knowledge determination with the aim of facilitating librarians and librarians in retrieval of collections in the library. This study uses the library research method by comparing the classification systems in 5 libraries from 5 different journals. The results of the study indicate that there are different implementation of classification systems depending on the type of library. The classification system used is Dewey Decimal Classification (DDC), Universal Decimal Classification (UDC), Mandala Classification, Classification System Libraries, Department of Orthotics, Prosthetics, Health Polytechnic, Ministry of Health, Jakarta and Archaeological Library Classification System. The conclusion can be used any classification system as long as it still has the same goal, which is to make it easier for librarians and users to find the desired source of information.